2004
DOI: 10.1080/00480169.2004.36387
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Brandenburg - emergence of a new strain affecting stock and humans in the South Island of New Zealand

Abstract: Important features of this disease are its high morbidity and mortality within a flock or herd, rapid local spread and its role as an occupational, health and safety risk to farm workers and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…S. Brandenburg has also been isolated from humans and other animals, including horses, cattle, goats, deer, pigs and dogs. In New Zealand, human cases occurred through contact with infected animals and not through consumption of animal products (Clark et al, 2004). Therefore, rapid detection of S. Brandenburg would aid in controlling the spread of this pathogen to both animals and humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. Brandenburg has also been isolated from humans and other animals, including horses, cattle, goats, deer, pigs and dogs. In New Zealand, human cases occurred through contact with infected animals and not through consumption of animal products (Clark et al, 2004). Therefore, rapid detection of S. Brandenburg would aid in controlling the spread of this pathogen to both animals and humans.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1996, Salmonella enterica serovar Brandenburg has been a major cause of ovine abortions and mortality, leading to significant economic impact to farmers in New Zealand (Clark, 2000;Clark et al, 2004;Roe, 1999;Smart, 2000). Sheep that have recovered from clinical disease may become carriers and excrete organisms in faeces.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36] For example, epidemics of salmonellosis in wild bird populations, which could be enhanced by temperaturedependent transmission, have also been identified as a source of human disease in the South Island of NZ. 37,38 Similarly, it is plausible that these more 'distal' temperature effects could operate in food growing areas (for example through contamination of grain, fruit, vegetables and others foods) that are removed in time and place from where these contaminated foods are subsequently consumed. Findings from these studies suggest the need for more sophisticated investigation to identify and control these more distant sources of salmonellosis.…”
Section: Discussionmentioning
confidence: 99%
“…The histopathological findings were consistent with an acute septicaemia in both cases. In 2004, Clark et al (2004) reported the emergence of a new strain of Salmonella Brandenburg affecting livestock, including deer, and humans in New Zealand. Salmonella Saint Paul was isolated from 16 out of 30 samples from a consignment of farmed venison sampled in one New Zealand game packing house but no Salmonella spp.…”
Section: Epidemiological Linkmentioning
confidence: 99%